METHODOLOGY FOR THE IDENTIFICATION OF TOURIST CLUSTERS: THE EXAMPLE OF THE REGIONS OF UZBEKISTAN - Dilbar ?asanovna Aslanova, Mashhura Toir?onovna Alimova (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article proposes an algorithm for identifying and assessing the possibilities of forming regional tourist clusters, which characterizes the most important cluster features and characteristics that can be quantitatively analyzed, and that allow developing strategic directions of regional cluster policy. Based on the application of the developed algorithm, quantitative estimates of the localization coefficients were obtained, characterizing the concentration of tourism infrastructure in a particular region. Based on the developed methodology for the identification of tourist clusters, based on localization coefficients, the analysis of the possibility of forming a regional tourist cluster in the Samarkand region of the Republic of Uzbekistan is carried out. Key words: cluster, identification, method, localization, factor analysis, quantitative methods, qualitative methods, index, coefficient, region